Interaction of Heparin with Lipoproteins – Role of the Complex in the Inactivation of Thrombin and Plasmin - Kecskés, E; Büki, K G; Bauer, P I; Machovich, R; Horváth, I (Thrombosis and Haemostasis, 1983)
Heparin forms a complex with human low density lipoprotein (LDL) in the presence of Ca2+. The complex is dissociable by 0.5 M NaCI. Thrombin and plasmin causes the dissociation of the LDL-heparin complex, whereas factor Xa does not. Heparin, complexed with LDL, retains its enhancing effect on the rate of thrombin and plasmin inactivation by antithrombin III. LDL isolated from the plasma of persons with different pathological conditions did not alter the rate of thrombin inactivation by antithrombin III either in the absence or in the presence of heparin. Heparin seems to maintain its biological functions when it is in a complex with LDL.
Keywords: Heparin; High density lipoproteins; Low density lipoproteins; Thrombin; Plasmin; Factor Xa; Antithrombin III